Genetic diversity and selection within natural dura oil palm accessions collected in Ghana for oil palm productivity improvement - Dickson Osei Darkwah; Essie Blay; Harry Amoatey; Enoch Sapey; Claude Bakoume; Daniel Agyei-Dwarko (Society for Indonesian Biodiversity, 2020)
Abstract. Darkwah DO, Blay E, Amoatey H, Sapey E, Bakoume C, Agyei-Dwarko D. 2020. Genetic diversity and selection within natural dura oil palm accessions collected in Ghana for oil palm productivity improvement. Biodiversitas 21: 3534-3538. The genetic base of oil palm breeding stock of the Ghanaian Oil Palm Research Institute is considered narrow after two selection cycles. Therefore, 79 accessions of natural dura oil palm collected in Ghana and conserved at Oil Palm Research Institute (OPRI) were field evaluated for 18 agro-morphological traits. ANOVA revealed differences among the 79 dura oil palm accessions for 14 traits. The most heritable traits were single fruit weight (h2 = 0.85), leaf area index (h2 = 0.63), bunch weight (h2 = 0.52), total leaf area (h2 = 0.51), and fresh fruit bunch (h2 = 0.46). Genetic coefficients of variation ranged from 3.30% for frond dry weight to 68.74% for total bunch weight denoting possibility of selection of desirable traits for improvement. Five high fresh fruit bunch yielding accessions (FFB ? 10.81 t/ha) with good heritable bunch characteristics were selected for introduction in the breeding stocks. In fact, their bunch number, average bunch weight, and mesocarp to fruit were higher, in absolute terms, than the controls and trial mean obtained in the study. Although, the height increment was close to those of the controls, short progenies are expected among descendants from their selfings or crosses.